METAL ORGANIC FRAMEWORKS HKUST-1 BASED CATALYST DESIGN FOR OXYGEN REDUCTION REACTION - Listanto R. NIM : 13313079, Virgiawan
Oxygen Reduction Reaction (ORR) is one of the important reactions with many influential uses in various fields. Fuel cells are one of the electrochemical cells that can not be separated from the ORR. ORR becomes an important component in the fuel cell to generate electrical energy, but it is a very slow reaction. Generally the catalyst used to accelerate ORR in the hydrogen fuel cell (PEMFC) is Platina (Pt). However, due to the relatively expensive price of Pt, it makes the fuel cell less desirable to be used extensively. Therefore, non-Pt catalysts needs to be developed to reduce the price of fuel cell. In this final project, Metal-Organic Frameworks (MOF) HKUST-1 is proposed to be a prospective ORR catalyst replacement of Pt. The study is conducted theoretically using calculations based on density functional theory using B3LYP as the exchange-correlation parameter and 6-311++G(d,p) as the basis set parameter. The reason for doing theoretical research is to facilitate the study and reduce the cost of research compared to the experimental study. This research will be focused on modeling the adsorption process and the dissociation of oxygen molecules on the cluster cage of MOF HKUST-1. The calculation focuses on the adsorption and dissociation process of oxygen molecules because these two stages are the determinants of the occurrence or absence of ORR. The modeling results show that O2 bond with the MOF cage cluster can occur on all tested metal atoms. The two strongest structures in adsorbing O2 are MOF-Fe with Eads of -0.71 eV and MOF-Mn with -1.27 eV. The entire structure under test adsorbs Oxygen with end-on configuration. Based on the literature, adsorption with this configuration will likely produce Hydrogen Peroxide. Meanwhile, the O2 dissociation model on the MOF structure shows that dissociation can not take place. The result of the study states that only the adsorption phase at ORR is met. Therefore, the conclusion drawn from the research of this final project is the cluster structure of MOF cage can not catalyze ORR well.